Attitudes to physical healthcare in severe mental illness; a patient and mental health clinician qualitative interview study - Butler, J; de Cassan, S; Turner, P; Lennox, B; Hayward, G; Glogowska, M (BioMed Central, 2020)
Background People with severe mental illness experience physical health significantly worse than the general population. Physical health monitoring is shared between primary care and secondary mental healthcare services, though there is debate whether mental health teams should provide more physical healthcare. The views of mental health clinicians and patients with mental illness towards physical healthcare provision are unclear. Aims To explore the attitudes of Community Mental Health Team (CMHT) clinicians and patients experiencing severe mental illness towards physical healthcare and its provision. Design and setting Qualitative study in a CMHT setting. Methods Interviews were carried out with CMHT clinicians and patients with severe mental illness. Data were collected using semi-structured interviews and analysed using thematic analysis. Results There were 14 patients and 15 clinicians recruited. Patients varied in their awareness of the association between physical and mental health, but were engaged in physical health monitoring. Clinicians were aware of the importance of physical healthcare but reported barriers to provision, including lack of training, resource constraints and uncertainty in their role. There was no consensus in either group regarding how physical healthcare should be provided, with diverse attitudes expressed for why CMHTs should and shouldn’t provide more physical healthcare. Conclusions Increasing physical healthcare provision from mental health teams requires healthcare-related barriers be addressed, but it remains unclear whether CMHT clinicians or patients believe this to be a solution.